UK reveals new platform for infrastructure data analysis and simulation modelling. Issue 3 (June 2019) - Hall, Jim
Abstract : A prototype of the UK's new Data and Analytics Facility for National Infrastructure was launched in June 2019 prior to being fully operational in 2022. Jim Hall of the University of Oxford explains its many benefits to civil engineers.